Материалы по фауне и зоогеографии пилильщиков (Hymenoptera, Symphyta) Большого Кавказа в пределах Азербайджана - Мамедова, Т.Г.; Ермоленко, В.М. (Вестник зоологии, 1982)
A faunistic survey incorporated 83 sawfly species of the Southern slope of Caucasus Major within Azerbaijan. The data on habitat distribution and zoogeographic analysis.